La calidad de vida en el personal de salud, que presentan Burnout en el Área Clínica de los servicios de emergencia y consulta externa del Hospital General Isidro Ayora. - Cañar Sarango, Erick Stiwar (2017)
Burnout Syndrome is a disorder that is caused by the constant emotional, social and work pressure in the person. The most affected professionals by this syndrome are doctors and other health workers, especially because of the constant changes in schedule and involvement in patients' problems. In the present investigation, we detected the presence of burnout, investigate the quality of life and determine the relationship between Burnout and quality of life of the health personnel working in the clinical area of the emergency and external consultation services of the Hospital General Isidro Ayora of the city of Loja. A non-probabilistic sample of 65 people was used, with which the quantitative-qualitative and descriptive study was carried out, supported by the use of instruments of high validity and reliability, such as the Maslach Burnout Inventory, which allowed the presence or absence to be detected of burnout syndrome and the quality of life scale that helped to know the quality of life maintained by health workers. The results of the investigation reveal the presence of Burnout Syndrome in 43.08% of health workers, while in terms of quality of life, professionals show that 92.31% of health personnel have a Good life quality. The contribution of the present investigation is a psychoeducational plan aimed at the prevention of Burnout and improvement of the Quality of Life directed to the health workers who work in the services of emergency and external consultation of General Hospital Isidro Ayora of the City of Loja. Keywords: Quality of Life, Burnout, Psychoeducational Plan, Stress.